The Unusual Suspects in Cytokinesis: Fitting the Pieces Together - Nguyen, Ly T. S.; Robinson, Douglas N. (Frontiers in Cell and Developmental Biology, 2020)
Cytokinesis is the step of the cell cycle in which the cell must faithfully separate the chromosomes and cytoplasm, yielding two daughter cells. The assembly and contraction of the contractile network is spatially and temporally coupled with the formation of the mitotic spindle to ensure the successful completion of cytokinesis. While decades of studies have elucidated the components of this machinery, the so-called usual suspects, and their functions, many lines of evidence are pointing to other unexpected proteins and sub-cellular systems as also being involved in cytokinesis. These we term the unusual suspects. In this review, we introduce recent discoveries on some of these new unusual suspects and begin to consider how these subcellular systems snap together to help complete the puzzle of cytokinesis.